2021
DOI: 10.1007/s13595-021-01060-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the non-growing season soil heterotrophic respiration rate are driven by environmental factors after fire in a cold temperate forest ecosystem

Abstract: & Key message During the non-growing season, environmental factors changed after fire, leading to significantly increased nongrowing season soil heterotrophic respiration (R h ) and potentially decreasing the amount of net C stored in cold temperate forest ecosystems of China. & Context Intensifying forest fire regimes are likely to influence future C budgets of forest ecosystems. However, the mechanism of fire disturbance on the components of non-growing season soil respiration rate (R s ) and its environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Furthermore, the lower R s rates in the postfire area compared with the undisturbed forest could also be partly explained by the destructive effects of wildfires on soil organic matter, aboveground vegetation, roots, and soil organisms. Although some authors observed increased R s rates in postfire areas during the growing season (e.g., Hu et al, 2021;Maljanen et al, 2006;Masyagina et al, 2016;Wang, Yao, et al, 2021) due to the release of nutrients (Ca, P, K, and Mg), except N, increased soil pH in the mineral soil layer due to ashes (Ernfors et al, 2010;Maljanen et al, 2006;Moilanen et al, 2012), improved litter quality (Stirling et al, 2019), and increased C/N ratio and electrical conductivity (EC) (Francos et al, 2019), the winter R s rates showed a different trend, probably due to the combined inhibitory effects of destructive effects of wildfires and freezing temperature on R s rates. Forest fires result in the destruction of the autotrophic and heterotrophic organisms in the active layer depths of the soil, alteration of the chemical and biological components (Masyagina et al, 2016), and reduction in the quantity of soluble C and microbial activities (Francos et al, 2019;Hobley et al, 2019).…”
Section: Ta B L Ementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the lower R s rates in the postfire area compared with the undisturbed forest could also be partly explained by the destructive effects of wildfires on soil organic matter, aboveground vegetation, roots, and soil organisms. Although some authors observed increased R s rates in postfire areas during the growing season (e.g., Hu et al, 2021;Maljanen et al, 2006;Masyagina et al, 2016;Wang, Yao, et al, 2021) due to the release of nutrients (Ca, P, K, and Mg), except N, increased soil pH in the mineral soil layer due to ashes (Ernfors et al, 2010;Maljanen et al, 2006;Moilanen et al, 2012), improved litter quality (Stirling et al, 2019), and increased C/N ratio and electrical conductivity (EC) (Francos et al, 2019), the winter R s rates showed a different trend, probably due to the combined inhibitory effects of destructive effects of wildfires and freezing temperature on R s rates. Forest fires result in the destruction of the autotrophic and heterotrophic organisms in the active layer depths of the soil, alteration of the chemical and biological components (Masyagina et al, 2016), and reduction in the quantity of soluble C and microbial activities (Francos et al, 2019;Hobley et al, 2019).…”
Section: Ta B L Ementioning
confidence: 99%
“…However, reported observations on the effects of fire on R s rates are not consistent, with some authors reporting an increase in R s due to enhanced heterotrophic respiration rates (Hu et al, 2021;Wang, Chen, et al, 2021;Wang, Yao, et al, 2021) while others reporting a decrease due to suppressed microbial activities and reduced microbial biomass (Chen et al, 2019;Hu et al, 2023). Kong et al (2019) reported no R s changes regardless of fire intensity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation